Genetic Diversity of Hair Colour in Horses - Tóth, Zsuzsanna (Acta Agraria Debreceniensis, 2005)
The main aim of this study was to analyze sources of variability for coat colour expressed as a quantitative trait as well as to determine non genetic factors influencing horse colour variation and shades. Traditional Hungarian horse breeds such as Lipizzan (grey), Gidran (chestnut), Shagya Arabian and Arabian Pure Bred (grey) and Nonius (bay and black) horses were involved in the current study. We report results using direct measurements of horse coat colour using objective colorimetric dimensions and a spectrophotometer for determining hair melanin. Correlation analysis indicated that the single biological component that correlated best with the total melanin content of horse hair is the L* value (r=-0.858, p